Life‐time prevalence and psychosocial correlates of adolescent direct self‐injurious behavior: A comparative study of findings in 11 European countries. (12th November 2013) - Brunner, Romuald; Kaess, Michael; Parzer, Peter; Fischer, Gloria; Carli, Vladimir; Hoven, Christina W.; Wasserman, Camilla; Sarchiapone, Marco; Resch, Franz; Apter, Alan; Balazs, Judith; Barzilay, Shira; et al.
<x xml:space="preserve">Abstract</x> Objectives To investigate the prevalence and associated psychosocial factors of occasional and repetitive direct self‐injurious behavior (D‐SIB), such as self‐cutting, ‐burning, ‐biting, ‐hitting, and skin damage by other methods, in representative adolescent samples from 11 European countries. Methods Cross‐sectional assessment of adolescents was performed within the European Union funded project, Saving and Empowering Young Lives in Europe (SEYLE), which was conducted in 11 European countries. The representative sample comprised 12, 068 adolescents (F/M: 6, 717/5, 351; mean age: 14.9 ± 0.89) recruited from randomly selected schools. Frequency of D‐SIB was assessed by a modified 6‐item questionnaire based on previously used versions of the Deliberate Self‐Harm Inventory (DSHI). In addition, a broad range of demographic, social, and psychological factors was assessed. Results Overall lifetime prevalence of D‐SIB was 27.6%; 19.7% reported occasional D‐SIB and 7.8% repetitive D‐SIB. Lifetime prevalence ranged from 17.1% to 38.6% across countries. Estonia, France, Germany, and Israel had the highest lifetime rates of D‐SIB, while students from Hungary, Ireland, and Italy reported low rates. Suicidality as well as anxiety and depressive symptoms had the highest odds ratios for both occasional and repetitive D‐SIB. There was a strong association of D‐SIB with both psychopathology and risk‐behaviors, including family related neglect and peer‐related rejection/victimization. Associations between psychosocial variables and D‐SIB were strongly influenced by both gender and country. Only a minor proportion of the adolescents who reported D‐SIB ever received medical treatment. Conclusion These results suggest high lifetime prevalence of D‐SIB in European adolescents. Prevalence as well as psychosocial correlates seems to be significantly influenced by both gender and country. These results support the need for a multidimensional approach to better understand the development of SIB and facilitate culturally adapted prevention/intervention.